Kimura’s Disease without Peripheral Eosinophilia: An Unusual and Challenging Case Simulating Venous Malformation on Imaging Studies-Case Report and Review of literature - Dokania, Vivek (J Clin Diagn Res, 2017)
Kimura’s Disease (KD) is a rare chronic inflammatory disorder presenting as multiple painless solitary subcutaneous nodules, predominantly in the head and neck region and frequently associated with regional lymphadenopathy and/or salivary gland involvement. Because of painless nature and indolent course, there is usually a delay in the patient’s presentation. KD may radiologically mimic other chronic inflammatory conditions like tuberculosis, vascular malformations and neoplasms. Clinical correlation and histological evaluation along with elevated peripheral eosinophil and serum IgE level are considered important for confirmatory diagnosis. We report a case of painless swelling over right submandibular region extending to the right superficial parotid. The haematological reports were within normal limits. Ultrasound (USG), Magnetic Resonance Imaging (MRI) and Magnetic Resonance Angiogram (MRA) favoured a diagnosis of venous malformation. However, histopathological examination of excised lesion confirmed a diagnosis of KD. This case proves the possibility of the KD even in the absence of peripheral eosinophilia and/ or elevated serum IgE level, and may mimic venous malformation on imaging studies. Therefore, KD must find a place in the differentials of solitary painless neck swelling even in the absence of peripheral eosinophilia and/or elevated IgE level.